Investigating Keyword Method in Teaching English Vocabulary for Junior High School with Special Needs Student - Triska Ernita Siregar (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
This study aimed to see whether the Keyword Method could be used to teach English vocabulary for special needs student. This research used descriptive qualitative method as the research design. Throughout the research, quiz and test scores improved. The Keyword Method has been proven to be an effective teaching tool through extensive research. It improves the concreteness and meaning of newly acquired information, and the Keyword Method connects newly learned information to previously stored knowledge.